Statistical Learning Signals for Complex Visual Images in Macaque Early Visual Cortex - Vergnieux, Victor; Vogels, Rufin (Frontiers in Neuroscience, 2020)
Animals of several species, including primates, learn statistical regularities of their environment. In particular, they learn temporal regularities that occur in streams of visual images. Previous human neuroimaging studies reported discrepant effects of such statistical learning, ranging from stronger occipito-temporal activations for sequences in which image order was fixed, compared with sequences of randomly ordered images, to weaker activations for fixed order sequences compared with sequences that violated the learned order. Several single unit studies in macaque monkeys reported that after statistical learning of temporal regularities, inferior temporal neurons show reduced responses to learned fixed order sequences of visual images compared with random or mispredicted sequences. However, it is unknown how other macaque brain areas respond to such temporal statistical regularities. To address this gap, we exposed rhesus monkeys (Macaca mulatta) to two types of sequences of complex images. “Regular” sequences consisted of a continuous stream of quartets, and within each quartet, image order was fixed. The quartets themselves were displayed, uninterrupted, in random order. The same monkeys were exposed to sequences of other images, having a pseudorandomized order (“Random” sequence). After exposure, both monkeys were scanned with fMRI using a block design with 3 conditions: regular sequence, random sequence and fixation-only blocks. A whole brain analysis showed a reduced activation in mainly occipito-temporal cortex for the regular compared to the random sequences. Marked response reductions for the regular sequence were observed in early extrastriate visual cortical areas, including area V2, despite the use of rather complex images of animals. These data suggest that statistical learning signals are already present in early visual areas of monkeys, even for complex visual images. These monkey fMRI data are in line with recent human fMRI studies that showed a reduced activation in early visual areas for predicted compared with mispredicted complex images.